Electron heating and energy inventory during asymmetric reconnection in a laboratory plasma. Issue 9 (11th September 2017) - Yoo, Jongsoo; Na, Byungkeun; Jara‐Almonte, J.; Yamada, Masaaki; Ji, Hantao; Roytershteyn, V.; Argall, M. R.; Fox, W.; Chen, Li‐Jen
Abstract: Electron heating and the energy inventory during asymmetric reconnection are studied in the laboratory plasma with a density ratio of about 8 across the current sheet. Features of asymmetric reconnection such as the large density gradients near the low‐density side separatrices, asymmetric in‐plane electric field, and bipolar out‐of‐plane magnetic field are observed. Unlike the symmetric case, electrons are also heated near the low‐density side separatrices. The measured parallel electric field may explain the observed electron heating. Although large fluctuations driven by lower hybrid drift instabilities are also observed near the low‐density side separatrices, laboratory measurements and numerical simulations reported here suggest that they do not play a major role in electron energization. The average electron temperature increase in the exhaust region is proportional to the incoming magnetic energy per an electron/ion pair but exceeds scalings of the previous space observations. This discrepancy is explained by differences in the boundary condition and system size. The profile of electron energy gain from the electric field shows that there is additional electron energy gain associated with the electron diamagnetic current besides a large energy gain near the X line. This additional energy gain increases electron enthalpy, not the electron temperature. Finally, a quantitative analysis of the energy inventory during asymmetric reconnection is conducted. Unlike the symmetric case where the ion energy gain is about twice more than the electron energy gain, electrons and ions obtain a similar amount of energy during asymmetric reconnection. Plain Language Summary: In the Magnetic Reconnection Experiment at Princeton Plasma Physics Laboratory, quantitative studies of magnetic reconnection have been performed over the last two decades. In this study, we present results from asymmetric reconnection, which occurs at the dayside magnetopause. We observed remarkable similarities between space and laboratory data regarding general features of asymmetric reconnection, which verifies earlier space observations. In addition, we carried out quantitative analysis on the electron heating and concluded that the electric field along the magnetic field plays an important role. Finally, the energy inventory, which regards how much of the magnetic energy is converted different forms of energy during reconnection, is carried out in this asymmetric laboratory plasma and shows similarities and differences, compared to the previous symmetric case. This quantitative study of the energy inventory is difficult to achieve via space data due to the limitation of the space measurements such as the number of data points, although it is important since the most important feature of magnetic reconnection is the ability to convert magnetic energy to plasma energy. Key Points: Features of asymmetric reconnection such as bipolar Hall magnetic fields are confirmed in laboratory Electron heating near the low‐density side separatrices is mainly caused by the parallel electric field The energy inventory of MRX asymmetric reconnection shows comparable ion and electron energy gains